Comparative Analysis Of Land Space And Structural Facilities In Relation To Academic Output - Oluwatade, Ijagbemi Christopher (Advances in Social Sciences Research Journal, 2019)
The goal for attainment of sustainable infrastructure for cities and communities of the world was set to be attained latest by year 2030. Goal 11 of the Sustainable Development Goals (SDGs) specifically is about making cities and human settlements inclusive, safe, resilient and sustainable. This paper in consideration of this laudable goal considers vertical developments incorporating mixed use as an option to lateral development in educational institutions communities in Nigeria. Data were collected from selected educational institutions in Nigeria and were compared with similarly selected educational institutions outside Nigeria using internationally accepted ranking criteria as basis to see if possessing excessive land mass as observed in Nigerian Universities will lead to better academic performance and better world ranking as witnessed in foreign Universities. The result shows that total land mass available to educational institutions outside Nigeria is minimal, more productively used and effectively maintained in a sustainable manner than land available to higher institutions in Nigeria where land is awkwardly used and wasted. Higher Institutions should center more on research and academic excellence rather than possessing massive lands that are not effectively maintained. This work therefore recommends that Authorities in Nigeria should reduce land mass requirement for establishment of higher institutions and mandate investors to develop vertically by applying the mixed use concept.